2018
DOI: 10.1111/nyas.13531
|View full text |Cite
|
Sign up to set email alerts
|

Misfolded proinsulin in the endoplasmic reticulum during development of beta cell failure in diabetes

Abstract: The endoplasmic reticulum (ER) is broadly distributed throughout the cytoplasm of pancreatic beta cells, and this is where all proinsulin is initially made. Healthy beta cells can synthesize 6000 proinsulin molecules per second. Ordinarily, nascent proinsulin entering the ER rapidly folds via the formation of three evolutionarily conserved disulfide bonds (B7-A7, B19-A20, and A6-A11). A modest amount of proinsulin misfolding, including both intramolecular disulfide mispairing and intermolecular disulfide-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 162 publications
5
50
0
1
Order By: Relevance
“…In mammals, proinsulin synthesis constitutes~30-50% of the total protein synthesis in the β cell 36 , and the ms 2 t 6 A modification in tRNA Lys UUU may be critical for efficient and accurate proinsulin translation. In agreement with studies in Cdkal1 β-cell KO mice 20 , proinsulin accumulation in Irp2-deficient INS-1 cells is associated with UPR activation of PERK-dependent eIF2α phosphorylation, which is known to reduce global translation [26][27][28] . Because β-cell mass was not reduced in 2.5-and 7.5-month-old Irp2 −/− mice, this suggests that phosphorylated eIF2α-mediated translational attenuation may allow Irp2-deficient β cells to adapt to cellular iron deficiency, thereby providing protection against UPR activation of apoptotic signaling pathways.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In mammals, proinsulin synthesis constitutes~30-50% of the total protein synthesis in the β cell 36 , and the ms 2 t 6 A modification in tRNA Lys UUU may be critical for efficient and accurate proinsulin translation. In agreement with studies in Cdkal1 β-cell KO mice 20 , proinsulin accumulation in Irp2-deficient INS-1 cells is associated with UPR activation of PERK-dependent eIF2α phosphorylation, which is known to reduce global translation [26][27][28] . Because β-cell mass was not reduced in 2.5-and 7.5-month-old Irp2 −/− mice, this suggests that phosphorylated eIF2α-mediated translational attenuation may allow Irp2-deficient β cells to adapt to cellular iron deficiency, thereby providing protection against UPR activation of apoptotic signaling pathways.…”
Section: Discussionsupporting
confidence: 88%
“…The UPR is activated in Irp2-depleted insulinoma cells. Accumulation of proinsulin in the endoplasmic reticulum (ER) lumen can lead to its misfolding or unfolding triggering ER stress and activating the unfolded protein response (UPR) 26 . Increased proinsulin levels in Irp2-deficient INS-1 cells suggested that the UPR might be activated in these cells.…”
Section: Irp2mentioning
confidence: 99%
“…More than 60% of the identified mutant alleles have been predicted or experimentally confirmed to impair oxidative folding of proinsulin in the ER (1,22). Importantly, these misfolded MIDY mutants not only fail to exit from the ER, but also physically attack co-expressed proinsulin-WT, impairing the folding and ER export of co-expressed proinsulin-WT, decreasing insulin production, and initiating insulin-deficient diabetes (12,20,23).…”
Section: Discussionmentioning
confidence: 99%
“…The above considerations culminate in a key question: how long is an untranslocated preproinsulin molecule allowed to spend in the cytosol before it is deemed unable to complete translocation and is targeted for degradation, and what mechanism initiates the switch from translocation to degradation? Once this is known, it should be possible to test the question of whether ER stress causes accumulation of undegraded preproinsulin molecules and/or contributes to β‐cell failure in type 1 or type 2 diabetes?…”
Section: Future Perspectivesmentioning
confidence: 99%